Pendekatan deadification dan pemanfaatan thymolvapor dalam Sistem Administrasi Pengelolaan dan Perawatan Aset Sekolah - Ronald Jolly Pongantung; Hascaryo Pramudibyanto; Cynthia Maria Siwi; Joutje Moonik (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2023)
This study aims to determine the ability of teachers to maintain school assets in the form of teaching materials. Teaching materials are learning resources that need to be preserved in quality to have a longer lifespan. Wellmaintained and managed teaching materials will always be clean and can be returned to the school library in good condition, making the administrative management easier. This study is directed towards teachers who directly utilize teaching materials, thus making them responsible for the sustainability of these teaching materials. Respondents come from rural teachers, but in reality, they have easy access due to the good quality of infrastructure and internet network, resulting in no significant obstacles in obtaining information about the deadification and utilization of thymolvapor on teaching materials. Similarly, the presence of ventilation and room cooling equipment is available in classrooms, meeting the requirements. The conclusion drawn is that there has been no effort in the deadification and utilization of thymolvapor on teaching materials due to the lack of knowledge about its proper usage. Therefore, efforts are needed, such as developing a brochure containing information about the importance of preserving teaching materials as school assets.